The Current international financial crisis and its impact on Latin America and the Caribbean (UN ECLAC SantiagoCL, 2009)
Argues that the region needs to formulate a new development agenda, one that leaves the so-called Washington consensus behind and that permits the removal of major long-standing obstacles to economic growth.
Keywords: ECONOMIC RECESSION